TRANSPARANSI SISTEM MANAJEMEN PENDIDIKAN ISLAM BERBASIS WEB DI ERA DIGITAL - Rusyunizal, Dori; Karim, Hamdi Abdul (Jurnal Manajemen Pendidikan, 2025)
The potential to integrate Sharia-compliant financial services into this management system could further enhance the effectiveness of financial management. This not only supports the economic independence of educational institutions but also empowers their operations in the long term. This study aims to examine how a web-based Islamic education management system can improve education transparency in the digital era. Using a qualitative approach through a literature study, this research found that a web-based management system provides easy access to real-time information to all education stakeholders, thus encouraging administrative efficiency, parental involvement and public oversight. The adoption of this system is proven to support more open and accountable management of finances, curriculum and infrastructure. However, there are significant challenges faced, such as limited digital infrastructure, low technological literacy of educators and data security issues. Therefore, the development of this system needs to be inclusive, sustainable and adaptive to local conditions to ensure the effectiveness of its implementation in Islamic education institutions.